Legal Protection for Village Credit Institutions as a Financial Business Entity Exploited to Resolve the Bad Credits in the Customary Village of Kerobokan - Anak Agung Sagung Laksmi Dewi; Desak Gde Dwi Arini; Ni Made Puspasutari Ujianti (Sociological Jurisprudence Journal, 2019)
The existence of customary rule sanctions in the resolution of the issues of bad credits within village credit institutions in the customary village of Kerobokan has been included as one of banking laws that is legally entitled to receive legal. This research aimed to the positioning of customary law sanctions in resolving bad loans at VCI Kerobokan Customary Village and to know the forms of legal protection for VCI and how are the bad loans of customers from outside the traditional villages in Kerobokan. The method used in this research is normative legal research, namely to conduct library research by reviewing literature and analyzing statutory regulations relating to applicable provisions on VCI. This research found the settlement of the bad credit at the customary village of Kerobokan is manifested into ways. The first through preventive legal efforts, that is to say, the very moment of signing the contracts, the customers are sure to have all their incumbencies. The second is through repressive efforts that must be made on the basis of good faith. The implementation of the civil law is that the form of retribution and customary law from the customary village. Keywords: Bad Credits; Legal Protection; Village Credit Institutions; Village-Owned Enterprises